THE CORPORATE PERFORMANCE MANAGEMENT METHODOLOGY, AS AN ANALYSIS TOOL FOR THE ORGANIZATIONAL BEHAVIOR - Trujillo, Emanuel; Romero,, Edna; Ortega, Nuria; Sánchez, Cristina (IJRDO - Journal of Business Management, 2017)
The performance management system has an indispensable place in the Company´s financialmanagement area, because it is essential that the organizational goals have a clear, correct andclose relation with the planning and financial control since the aforementioned, the administration might have a better perspective of the business situation and allow the soon andperiodical detection in opportunity areas, so that the best possible human and economic capital performance is obtained according to the operations annual plan, the above along with highlydynamic global economic conditions and competitive in the first 21st century decades cause astrong pressure on the continuous improvement of the business performance through the designand implementation of methods and flexible tools that meet the institutional needs,consequently, the investigation management performance and development is increasinglyimportant for all sectors, because the absence of a relationship budgetary strategyimplementation is susceptible of generating misleading effects or to turn the strategy into purely formal indicators